Stereotypes and valuations of Peruvian social groups in a sample of wealthy people from Lima - Pancorbo, Gina (2019)
Background: Peruvian society is characterized by its ethnical, cultural and socioeconomic diversity, which leads to complex intergroup relations. Objective: To contribute to understanding this phenomenon, the present study aims to examine the stereotypical representations and prejudice towards different Peruvian social groups by high-socioeconomic-status group members from Lima. Method: The research used a mixed-method design for complementing two different approaches: a quantitative one, where questionnaires were administered to a sample of 90 participants; and a qualitative one, in which semi-structured interviews were conducted with 10 participants. Results: The results showed that the participants identified high- and low-status groups in the Peruvian society, and hold ambivalent stereotypical representations towards them. The participants identified and valued White Peruvians as high-status group members, who are competent and developed but also corrupt. On the other hand, they identified and valued Amazonian and African Peruvians to a lesser extent, who are considered as low-status, undeveloped but joyful groups. Conclusion: The study emphasizes the importance of social class attributes used in the formation of stereotypical representations and prejudice towards different Peruvian social groups.